TINGKAT PENGETAHUAN MASYARAKAT TENTANG SWAMEDIKASI DI DESA KURIPAN KIDUL PEKALONGAN SELATAN - Agustin, Melina; Mursiany, Anita (Universitas Pekalongan, 2022)
ABSTRACT Self-medication or often referred to as self-medication is a way to get healing from a disease, among others, by going to a doctor or trying to treat it yourself. The reason for doing this research is because it looks at the factors that make self-medication activities high since the Covid-19 in Indonesia. People have a high enough sense of fear to visit a hospital or clinic because it is considered a place that has the potential to spread the Corona virus which makes people prefer to do self-medication to treat the disease they are experiencing. The purpose of this study was to determine the level of community knowledge about self-medication in Kuripan Kidul Village, South Pekalongan. This research is a non- experimental research conducted in Kuripan Kidul Village, South Pekalongan. The study was conducted with a cross-sectional design with the sampling technique used is simple random sampling (Simple Random Sampling). Respondents who took part in this study had to meet the inclusion criteria, namely all residents of Kuripan Kidul Village, South Pekalongan, aged > 18 years, respondents who were involved in this study wanted to sign informed consent and had done self-medication and exclusion criteria were working as medical personnel or other health workers. The results of the research that has been done regarding the level of knowledge of self-medication in the village of Kuripan Kidul Pekalongan Selatan, respondents with good knowledge are 75.76%, respondents with sufficient knowledge are 21.21%, and respondents with less knowledge are 3.03%. Keywords: Self-medication1, Knowledge2